Karyotype variation in Drosophila birchii - V. Baimai (2018)
Drosophila birchii, a member of the melanogaster species group of the subgenus Sophophora, is common in the tropical rain forests of the Australia-New Guinea areas. Chromosome squashes are easily prepared from the larval ganglion cells and the sex chromosomes are readily recognizable. The species exhibits a remarkable karyotype variation. The metaphase plate figures, in general, show two pairs of V's, one pair of dots and one pair of sex chromosomes. Variations in metaphase chromosome morphology are found in the X (with four types), the Y (with three types) and chromosome IV (with two types). Chromosomal interchanges between X- and Y-chromosomes Type I are postulated to be involved in the differentiation of sex chromosome morphology while the modification of chromosome IV seems likely to be a result of the acquisition of extra heterochromatin. These chromosome types form seven distinct metaphase plate figures, all encountered in wild populations, thus giving D. birchii the most variable karyotype in the genus Drosophila. © 1969 Springer-Verlag.